As disputas de narrativas sobre o “glorioso ato de 13 de Maio de 1888” nos jornais de Cachoeiro de Itapemirim-ES (1888-1889) (Ágora Journal, 2020)
By reading two newspapers published in the main coffee city of Espírito Santo during the 19th century (Cachoeiro de Itapemirim), it is intended to highlight tensions and contradictions in the construction of the memory of Abolition in Cachoeiro de Itapemirim Press, which enthusiastically received the “glorious act of May 13, 1888”. The analysis of the content, according to Lawrence Birdin and Renné Zicman’s directions, will be used in the research of O Cachoeirano and O Constitucional, which belong to political and ideological opposite fields. The research is between the Golden Law and the proclamation of the Republic and it reveals the development of contrasting narratives among themselves, ambiguous and changeable in the scenario marked by the growing tensions between monarchists and republicans and by the beginning of disputes for the memory of Abolition.
Keywords: Abolition; Press; Memory